Seismic performance assessment of low-rise precast wall panel structure with bolt connections. (15th February 2019) - Guo, Wei; Zhai, Zhipeng; Cui, Yao; Yu, Zhiwu; Wu, Xiaoli
Highlights: A novel low-rise precast wall panel structure system is proposed. Bolt loosening is proven to be critical to the dynamic responses. The lateral deformation mode of test structure is dominated by sliding of shear wall . Performance design objectives and damage limit states of the system are given, and the fragility curves are performed. The proposed novel precast structure system presents high stiffness, high load capacity and high collapse margin ratio. Abstract: This paper proposes a novel low-rise precast wall panel structure with bolt connections, which has advantages of convenient and rapid assembly. To investigate seismic performance of the structure system, a shaking table test of a 1/2 scaled three-story model is conducted, by which the structural dynamic responses, damage pattern, and seismic fragility are analyzed. The results show that the proposed novel precast structure system presents high stiffness, high load capacity and high collapse margin ratio. In this novel structure system, the bolt connections are critical for the structural dynamic characteristics and responses. Damage pattern of the structure follows the sequence of bolt loosening, adjoining wall panels sliding and dislocating, structural components cracking. The seismic damage of test structure is slight, and most structural components still remain elastic in maximum considered earthquakes. Based on the test results, performance design objectives for service level earthquake, design based earthquake and maximum considered earthquake are given, and four limit states are defined. The fragility curves of the structure are developed, as well as the fragility of nonstructural components.